NLRP3 in the Cerebrospinal Fluid as a Potential Biomarker for the Diagnosis and Prognosis of Community-Acquired Bacterial Meningitis in Adults - Gong, Zhe; Zhang, Chaopeng; Li, Yanfei; Jing, Lijun; Duan, Ranran; Yao, Yaobing; Teng, Junfang; Jia, Yanjie (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To discover the levels of NLR family pyrin domain-containing 3 (NLRP3) in the cerebrospinal fluid (CSF) from adult patients with community-acquired bacterial meningitis (CABM). Methods We enrolled 34 patients with CABM, 20 patients with viral meningitis (VM), and 25 patients with non-inflammatory neurological disease. Data on standard clinical parameters, scores, and outcomes were obtained from clinical records, and inflammasome levels in the CSF were measured by an enzyme-linked immunosorbent assay. The area under the receiver operating characteristic curve (AUROC) was used to quantify the diagnostic and prognostic performance of CSF NLRP3 as a biomarker of CABM. Results The levels of NLRP3 were elevated in the CSF of patients with CABM, but levels for ASC, caspase-1, or other inflammasomes did not vary significantly. CSF NLRP3 was positively correlated with clinical severity and with the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte count, albumin quotient (Qalb), and immunoglobulin G quotient (QIgG). Patients with unfavorable outcomes had higher levels of NLRP3 in the CSF, which were correlated with several blood indicators, including NLR, PLR, and lymphocyte and monocyte counts. Conclusions Our results suggested that the level of CSF NLRP3 could represent the severity of CABM in adults. CSF NLRP3 may be a good biomarker for the diagnosis of CABM and for the discrimination between CABM and VM. It may also be a better biomarker for predicting the prognosis of adult patients with CABM when compared to the NLR or the lymphocyte and monocyte counts.